Vigabatrin therapy in infantile spasms - Pongkiat Kankirawatana (2018)
Rationale: To determine the clinical outcome and side effects of vigabatrin (VGB) in the treatment of infantile spasms (IS) and its long-term outcome. Method: All children with IS treated with vigabatrin were studied. Clinical data regarding age of onset, duration of IS before therapy started, recurrence of IS, types of seizures that relapse, clinical outcome and side effects were monitored. Results: 36 children (17 girls, 19 boys) with IS participated in the study. The mean age of onset of IS was 115.55 ± 67.3 days old (range, 15 to 300 days). Six were cryptogenic IS and 30 were symptomatic IS. The etiologies of symptomatic IS in this study were tuberous sclerosis(6), hypoxic ischemic encephalopathy (HIE) / periventricular leukomalacia(11), porencephaly(1), partial agenesis of corpus callosum(1), hemimegalencephaly(1), cortical dysplasia(7), and microcephaly(3). 66.67 per cent (24 of 36) of patients responded to VGB within a mean 2.95 ± 2.25 days (range, 1 to 7 days). In those who responded to VGB, 3 patients developed recurrent IS within 69.3 ± 46.7 days (range, 30 to 121 days). Five patients developed epilepsy with different types of seizure during long-term follow-up. The mean duration of subsequent epilepsy after cessation of IS was 16.4 months (range, 5 months to 3 years 10 months). The mean duration of follow-up was 2.74 years (range, 1.09 years to 5.76 years). 10 patients were successfully weaned off VGB after a mean IS free period of 22.5 ± 5.5 months (range, 12 to 27 months). Transient drowsiness was seen in 4 patients. Three patients had transient abnormal sleep patterns and irritability. Visual field abnormalities were not found but difficult to assess fully in this study. Conclusion: VGB therapy has a high response rate for the control of IS and is well tolerated in most children. All patients who responded to VGB and were spasm free for more than one year were successfully weaned off VGB therapy. Because serious side effects such as visual field abnormalities are difficult to monitor, the authors propose that VGB could be withdrawn or switched to another AED after a spasm-free period of more than one year.